Development of Poster as Learning Media for Biology Course on Life and Environment Subject in Small Ecosystem Topic for Grade 12 Students of Sanpatong Wittayakom School, Chiang Mai - จองแดง, นัยนา; ปฐมอารีย์, วสุ (Progress in Applied Science and Technology, 2018)
This research objectives are 1) to develop a poster media for teaching microbiological techniques to analyze coliform bacterial contamination of drinking water in Lanna clay pot for Biology course on Life and Environment subject in small ecosystem topic 2) to develop students' academic achievement for Biology course on Life and Environment subject in small ecosystem topic 3) to study student satisfaction after using this poster for teaching. The research samples are 50 students purposively selected from Grade 12 students of Sanpatong Wittayakom school. The research tools are as follow 1) a unit lesson plan for 3 teaching periods 2) pre-test and post-test questions 3) a practice activities and 4) satisfactory questionnaire for students. The research process started with a pre-test for students before lesson. Then, the developed poster was used in the classroom. After that, a post-test was carried out. The results were as follows: 1) the efficiency of the developed poster (E1/E2 = 75.0/76.6) was higher than standard (70/70) 2) academic achievement of students in post-test was higher than pre-test (p < 0.05) and 3) students showed high satisfaction on using poster as teaching media.